Science and Politics - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2010)
Science is the function of constant thought and immediate action of a dedicated scientist. Scientific growth depends on intellectual and spiritual power of an individual. The government belonging to a political party largely influences the progress of science in a country. In many cases, politics dictate the governing of the research institutes and often act as hindrance in the progress of science. Scientific talent can never progress under suppressive and bureaucratic attitude of the administrator. The article reflects personal experiences and opinions of the author which is open to criticism